Bucking Coil Used in Airborne Transient Electromagnetic Survey - Chen Shudong; Wang Yujie; Zhang Shuang (2012 International Conference on Industrial Control and Electronics Engineering, 2012)
We have calculated and simulated B field along the radial of coil using MATLAB and MAXWELL. Then B field of the transmitting coil and the bucking coil of different radius are generated. Based on the results above, two methods of the magnetic offset are proposed, the B field offset method and magnetic flux offset method. Firstly, we talk about the magnetic field left along the radius of the coil. Secondly we calculate the magnetic flux left when using different radius of the bucking coil to obtain the best results. The magnetic moment of the bucking coil almost has no impact on the total magnetic moment.